Functions and cellular localization of cysteine desulfurase and selenocysteine lyase in Trypanosoma brucei - Poliak, Pavel; Van Hoewyk, Douglas; Oborník, Miroslav; Zíková, Alena; Stuart, Kenneth D; Tachezy, Jan; Pilon, Marinus; Lukes, Julius (The FEBS journal, 2010)
Nfs-like proteins have cysteine desulfurase (CysD) activity, which removes sulfur (S) from cysteine, and provides S for iron-sulfur cluster assembly and the thiolation of tRNAs. These proteins also have selenocysteine lyase activity in vitro, and cleave selenocysteine into alanine and elemental selenium (Se). It was shown previously that the Nfs-like protein called Nfs from the parasitic protist Trypanosoma brucei is a genuine CysD. A second Nfs-like protein is encoded in the nuclear genome of T. brucei. We called this protein selenocysteine lyase (SCL) because phylogenetic analysis reveals that it is monophyletic with known eukaryotic selenocysteine lyases. The Nfs protein is located in the mitochondrion, whereas the SCL protein seems to be present in the nucleus and cytoplasm. Unexpectedly, downregulation of either Nfs or SCL protein leads to a dramatic decrease in both CysD and selenocysteine lyase activities concurrently in the mitochondrion and the cytosolic fractions. Because loss of Nfs causes a growth phenotype but loss of SCL does not, we propose that Nfs can fully complement SCL, whereas SCL can only partially replace Nfs under our growth conditions.
Keywords: Genes, Protozoan; RNA interference; Mitochondria; RNA, Messenger; Carbon-Sulfur Lyases; Cell Compartmentation; fylogeneze; Phylogeny; cytosol; kompartmentace buňky; protozoální proteiny; RNA, Protozoan; Trypanosoma brucei brucei; Cytosol; protozoální geny; Animals; zvířata; lyasy štěpící vazby C-S; Lyases; RNA protozoální; Protozoan Proteins; lyasy; messenger RNA; RNA Interference; mitochondrie